2020
DOI: 10.1002/jwmg.21814
|View full text |Cite
|
Sign up to set email alerts
|

Bark Beetle‐Affected Forests Provide Elk Only a Marginal Refuge from Hunters

Abstract: For nearly 2 decades, the forests of the Rocky Mountains in the United States experienced a bark‐beetle (Dendoctronus ponderosae) epidemic. The number of dead and falling trees from this epidemic likely will affect how elk (Cervus canadensis) and hunters use the forest and their interactions. Downed trees potentially create a component of refuge habitat that could affect the effectiveness of hunting to regulate abundance of growing elk populations. We evaluated how forests affected by bark beetles in south‐cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…This is consistent with behavior during summer in previous studies on mule deer in arid climates (Hayes and Krausman 1993, Tull et al 2001, Ager et al 2003, Morano et al 2019), where deer are more active in foraging areas at night and select resting areas with moderate canopy cover during the day (other ungulates, Giotto et al 2013, Long et al 2014). During the rifle season, habitat use by males was not related to density of canopy, but males increased distance from motorized routes, suggesting that avoidance of human activity was a priority behavior, as is true during hunting season in other ungulates (white‐tailed deer [ Odocoileus virginianus ], Kilgo et al 1998; roe deer [ Capreolus capreolus ], Bonnot et al 2013; and elk, Proffitt et al 2013, Paton et al 2017, Spitz et al 2019, Lamont et al 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with behavior during summer in previous studies on mule deer in arid climates (Hayes and Krausman 1993, Tull et al 2001, Ager et al 2003, Morano et al 2019), where deer are more active in foraging areas at night and select resting areas with moderate canopy cover during the day (other ungulates, Giotto et al 2013, Long et al 2014). During the rifle season, habitat use by males was not related to density of canopy, but males increased distance from motorized routes, suggesting that avoidance of human activity was a priority behavior, as is true during hunting season in other ungulates (white‐tailed deer [ Odocoileus virginianus ], Kilgo et al 1998; roe deer [ Capreolus capreolus ], Bonnot et al 2013; and elk, Proffitt et al 2013, Paton et al 2017, Spitz et al 2019, Lamont et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, hunting season dates and types (i.e., rifle vs. archery; Proffitt et al 2009, Ranglack et al 2017, hunting modalities (i.e., foot vs. motorized ;Stankowich 2008), and the distribution of land management status can elicit variable behavioral responses in different species. In general, however, studies in western North America (Conner et al 2001;Vieira et al 2003;Proffitt et al 2009Proffitt et al , 2010Proffitt et al , 2013Ranglack et al 2017;DeVoe et al 2019) have reported habitat shifts toward refugia or security areas during hunting season (Mikle et al 2019, Lamont et al 2020. Specifically, disturbance from hunting can cause animals to move to areas farther from roads (Bonnot et al 2013, Paton et al 2017, DeVoe et al 2019, Spitz et al 2019, with higher canopy cover (Ranglack et al 2017), or restricted public access (Proffitt et al 2009(Proffitt et al , 2010Mikle et al 2019).…”
mentioning
confidence: 99%
“…Hunter Space Use and Roads Models of space use revealed strong links of most Starkey hunters, especially rifle deer hunters, with open roads during shooting hours, a behavior well-documented for elk (Lyon and Burcham 1998, Gratson and Whitman 2000b, Lamont et al 2020) and white-tailed deer (Stedman et al 2004) hunters. In Pennsylvania, nearly 90% of deer hunters remained within 0.5 km of a road (Diefenbach et al 2005).…”
Section: Space Use In Relation To Targeted Preymentioning
confidence: 99%
“…We determined that most stationary locations (i.e., consecutive locations in camp) were contained within a 200-m radius of the cluster centroid; thus, we excluded from analysis any telemetry locations within a 200-m radius of hunter camps. We further censored locations to exclude those obtained during the scouting period, outside legal shooting hours plus a 1-hour buffer before and after (Lamont et al 2020), within 300 m of the check station (Gerrits et al 2020), and after the day of harvest (successful hunters only; Plante et al 2017).…”
Section: Hunter Telemetry Datamentioning
confidence: 99%
See 1 more Smart Citation